Clinical practice guidelines and real-life practice on hepatocellular carcinoma: the Hong Kong perspective - Rex Wan-Hin Hui; Lung-Yi Mak; Tan-To Cheung; Victor Ho-Fun Lee; Wai-Kay Seto; Man-Fung Yuen (Clinical and Molecular Hepatology, 2023)
Hepatocellular carcinoma (HCC) is a major public health burden in Hong Kong, and chronic hepatitis B is the most common HCC etiology in our region. With the high case load, extensive local expertise on HCC has been accumulated. This article summarized local guidelines and real-life practice on HCC management in Hong Kong. For HCC surveillance, liver ultrasound and serum alpha-fetoprotein for periodic screening is recommended in viral hepatitis or cirrhotic patients, and this is adhered to in clinical practice. HCC diagnosis is not covered in local guidelines, yet our practice is in-line with regional guidelines, where diagnosis is usually achieved by cross-sectional imaging and without the need for histology. Our guidelines recommend using the Hong Kong Liver Cancer Staging for pre-treatment staging, yet we routinely use other widely-adopted systems such as the Barcelona Clinic Liver Cancer Staging and the Tumor-Node-Metastasis Staging as well. Our local guidelines have provided clear treatment algorithms for the whole range of HCC therapies, including resection, ablation, transplant, transarterial chemoembolization, transarterial radioembolization, stereotactic body radiation therapy, targeted therapy, and immunotherapy. Real-life treatment choices are largely in line with the guidelines, although treatment protocols are individualized, and availability of specific therapies can vary between centers. Overall, HCC guidelines in Hong Kong are tailored based on local expertise and our unique patient population. The guidelines are up-to-date and provide practical pathways to assist our routine practice. Regular updates of local guidelines are warranted to account for the rapidly evolving paradigm of HCC management.